Investigation of Fiber Optic Sensor based on Surface Plasmon Resonance for Sensing Applications - Singh, Sarbjit (Thapar Institute of Engineering and Technology, Patiala, 2020)
Surface plasmon resonance together with optical fiber technology has emerged as an encouraging application of optical bio-sensing in the present circumstances. It has made a significant contribution to certain measures in medical diagnosis. This technique permits the instant and extremely sensitive recognition of biological samples, with utilizations in medical diagnostics, ecological monitoring, and agriculture science etc. Surface plasmon resonance is most sought after technique with wide spread uses in the recognition of molecular biology interactions but certain modifications are necessary for both refractive index (RI) sensitivity and in-vivo uses for many scientific applications. Sensors manufactured using optical fiber offer significant advantages over traditional platforms, such as simple manufacturing process, small size and possibility for in situ and remote measurements. In present scenario, surface plasmon resonance technology has been incorporated into optical fiber for sensing applications. SPR technology is basically an optical phenomenon and involves the coating of metallic nanostructure materials of SPR nobel metals e.g. gold, silver, copper etc on optical fiber core. SPR has turn out as most important optical bio-sensing technique in the field of bio-chemistry and medicine science. The research presented in this thesis focuses on the optical fiber sensor based on surface plasmon resonance (SPR) technique for sensing applications. Metallic nanostructure material, when embedded on the core of fiber may be designed to support plasmonic resonance phenomenon and is usually perceptive to the sensing sample refractive index (RI). In the sensing region, various types of analyte such as glucose etc are used to test the sensing performance of the sensor. In case of angular interrogation and wavelength interrogation type of sensor, the identification of distinct refractive index (RI) may be accomplished by measuring resonant dip angle shift θRDA and resonant wavelength shift λreson of spectral intensity from TM-reflectance curve. Factors contributing to the analyte refractive index (RI) sensitivity are investigated methodically through modeling, simulating process and theoretical explanation. The refractive index (RI) sensitivity of optical sensing system may be customized through designing a applicable metallic structure with optimized parameters. This thesis highlights the basic theory and concepts of SPR technology. Fiber optic sensor with multilayer structure based on two-dimensional (2D) material and SPR nobel metal Au is proposed for achieving high sensitivity for glucose (i.e. sensing analyte) sensing. Multilayer stack consists of stack of four layers i.e. fiber core-Au metal-2D material graphene-sample layer. We have shown the use of a new type of 2D material, graphene in the sensing region for glucose sensing. 2D materials are the material consisting of single layer of atoms. It is worthwhile to mention here that optoelectronics using 2D material is interested subject of research in the present scenario. Therefore such types of material show extreme behaviour with properties which are observable at nanoscale dimensions but not observable at bulkscale (macro-scale). Different properties of active metals have also been studied and investigated in order to search the best suitable combination of noble metal, thickness and 2D material. The parameters related with plasma wavelength λplasma and collision wavelength λcollision are carefully studied and chosen. The well known Drude-Lorentz model has been considered for dielectric constant of SPR active metals and oxides metals. The effect of dielectric constant ℇmetal on the resonant shift has been examined as the plasmonic resonance phenomenon is exhibited by the active metal with negative real dielectric constant. The aforesaid design is simulated with multiple iterations in order get better shift of reflectance curve in response with the refractive index of glucose. It is analysed that the proposed sensor design of SPR sensor utilizing 2D material, Au film and graphene film exhibit extreme sensitivity, Sn ≈ 198°/RIU. Several parameters related with metal diffraction grating based SPR sensors are explored. It is analysed from the study of wave polarization techniques such as TM-polarization and TE-polarization that metallic gratings are highly sensitive to the incident electromagnetic (EM) wave polarization and only TM-polarization is associated with the excitation of surface plasmon politrons (SPPs). Using metal grating in the structure explore the advantage that the momentum component of the diffracted wave in parallel to the interface and the propagation constant of surface plasmons (SPs) are matched. The impact of sensor system parameters such as operating wavelength, the grating period T, type of nobel metal, and the RI of sensing sample nsense on the refractive index (RI) sensitivity are systematically studied. In accordance with the above observation, bimetallic diffraction grating (Au & Al) based SPR sensor is reported. By carrying out the simulation analysis, the resonant impact of bimetallic diffraction grating on the sensing enhancement is observed. The incident optical wave at metal grating is partly returned back and partly divided into sequences of diffracted waves or diffraction orders. It is observed that for the proposed geometry of the sensor, enhanced sensitivity is attained if -1st diffraction order of metallic grating is used to excite the surface plasmon waves (SPW). Active metal nanoparticles (NPs) have several benefits in a plethora of sensing applications. Gold nanorods (AuNRs) are sensitive to both refractive index (RI) change & nanorods (NRs) shape and their size. Circular AuNPs distinctively exhibit a unique intense absorption belt which does not exist in spectrum of the bulk scale gold. This intense absorption belt appears when the frequency of applied light photon is resonant with the combined oscillation of a free electron of nanoparticles (NPs). Consequently, the absorbance & peak wavelength of the NPs are perceptive to refractive index (RI) of the surrounding sample. Based on the study, the SPR sensor based on nanoparticle employing Au NR array is reported and its performance is observed with the help FEM simulation technique. It is analysed from the simulation results that the resonant wavelength λreson rises with rise in RI of the anlayte. The value of R-square, co-efficient of determination was calculated as 98.78 % & it is extremely high. Further results conclude that when the radius of circular AuNR is 60nm then the enhanced sensitivity, SAuNR ≈ 2200nm/RIU is presented by proposed geometry of the sensor for analyte recognition. Enhanced sensitivity and high R-square, co-efficient of determination (COD) are attained after geometric optimization. These sensors offer numerous advantages in bio-medical science, food processing, chemical species recognition & agriculture science. The study suggests that fiber optic sensor with SPR technology is beneficial for creating perfect sensing design. The research outcomes of the thesis have been published in various Science Citation Index (SCI) international referred journals as per publications list at page no (vi).
Keywords: Surface Plasmon, Optical Sensor, Sensitivity, Grating